KEPALA SEKOLAH SEBAGAI MANAJER DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SD NEGERI PAGERTOYA KEC. LIMBANGAN KAB. KENDAL - Sigit Rudiyanto; Iskadariyah; Hindun; Soedjono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims 1) to determine the role of school principals as managers in planning the implementation of the Independent Curriculum. 2) To find out the role of the school principal as a manager in organizing the implementation of the Independent Curriculum. 3) to find out the role of the school principal as a manager in implementing the Independent Curriculum. 4) to determine the role of the principal as a manager in supervising the implementation of the Independent Curriculum at the Pagertoya Limbangan Kendal Public Elementary School. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: a) the role of the school principal is managerial in planning by carrying out planning procedures including identification of needs, school programs, and socialization of school programs. b) the role of the school principal as managerial in organizing by carrying out organizing procedures including the placement of school resources, organizational development, assignment and delegation of authority. c) the role of the principal as managerial in implementation by carrying out mobilization procedures including directing the principal and motivating the principal. d) the role of the school principal as managerial in supervision by carrying out supervision procedures including assessment, evaluation of school activities, and follow-up.